Colon Cleansing for Colonoscopy in Patients with Ulcerative Colitis: Efficacy and Acceptability of a 2-L PEG Plus Bisacodyl Versus 4-L PEG. Issue 9 (September 2015) - Manes, Gianpiero; Fontana, Paola; de Nucci, Germana; Radaelli, Franco; Hassan, Cesare; Ardizzone, Sandro
Abstract : Background: Low-volume preparations are gaining attention for higher acceptability but have been never evaluated in IBD. We compare the efficacy, safety, and tolerability of a 2-L PEG with a 4-L PEG solution in patients with ulcerative colitis. Methods: This is a multicenter, randomized, single-blind study. Adult outpatients with ulcerative colitis undergoing colonoscopy received either 2-L PEG plus bisacodyl or 4-L PEG. Bowel cleansing was assessed using the Ottawa Scale and rated as adequate if the score was ⩽2 in each colon segment. Patient acceptance, satisfaction, and related symptoms were recorded. Results: Preparation was adequate in 80% of the 211 patients without any differences between groups. Mean Ottawa scores for whole and right colon were similar in the 2 groups. As concern tolerability, 83% patients in 2-L PEG arm and 44.8% in 4-L PEG arm reported no or mild discomfort ( P < 0.0001) and 94.3% and 61.9% expressed their willingness to repeat the preparation ( P < 0.001). Palatability was better with 2-L PEG, whereas related symptoms occurred more frequently with 4-L PEG. Regardless of preparation, split dosage was associated with better cleansing. Further predictors of poor cleansing were moderate/severe discomfort during preparation and more than 6 hours between end of preparation and colonoscopy. Extension and severity of colitis did not influence quality of preparation. Conclusions: Low-volume PEG is not inferior to 4-L PEG for bowel cleansing in ulcerative colitis, but it is better tolerated and accepted. The time interval from solution intake and colonoscopy is the most important factor affecting quality of cleansing in ulcerative colitis. Abstract : Article first published online 9 July 2015.Supplemental Digital Content is Available in the Text.